A rights-based approach to board quotas and how hard sanctions work for gender equality. Issue 4 (November 2019) - Humbert, Anne Laure; Kelan, Elisabeth K; Clayton-Hathway, Kate
This article examines whether progress in women's access to decision-making positions is best achieved through increased levels of development or targeted actions. Drawing on European data for the period 2006–2018, the article examines the association between how gender equal a country is and legislated measures such as board quotas with women's representation on boards. The analysis then explores how this can be nuanced by differentiating between hard sanctions, soft sanctions and codes of governance. It shows that board quotas cannot be relied upon as instruments of progress independently of a contextual environment that is more gender equal. Furthermore, board quotas with hard sanctions work best, followed by codes of governance, particularly when associated with higher gender equality. However, board quotas with soft sanctions are associated with results that are only marginally better than not having any measure in place. The article concludes that for further and faster progress to be made, introducing legislated board quotas shows great potential, though only in combination with striving for a gender equal society and using hard sanctions. The results call for organizations not to lose focus on 'rights' at the expense of the more palatable 'business case' for board quotas when striving for equality on corporate boards.